Syngas generation from thermochemical conversion of locally available biomass waste for automotive - Hagos, Ftwi Yohaness; Zailan, Roziah; Kulkarni, R. R.; Singh, Lakhveer (2019)
The growth of the world population as well as the ever-advancing development of the developing countries into industrialized countries leads to an increasing demand for energy and raw materials. As energy production increases, the emissions emitted increase as well. To counteract this pollution, the states adopt measures to reduce air pollution. The car industry is also affected. Lowering both, CO and NOX is the challenge. One possibility for the internal combustion engine is the use of alternative fuels to achieve this goal. These can reduce the emissions incurred. One alternative fuel is synthetic gas which consist primarily of hydrogen, carbon monoxide and often carbon dioxide. Using this gas the unburned hydrocarbons will decrease and an increase in thermal efficiency is to observe. To produce syngas, there are many reforming processes, each with its own benefits and disadvantages. This project has the task of designing an inline reformer for producing syngas in a retrofitted Otto internal combustion engine with natural gas. The fuel supply of the internal combustion engine has to be completely converted to a natural gas - syngas mixture. The engines demand for fuel should inherit a maximum amount of 15% syngas which will be mixed to the prime source, natural gas, after conversion.